Identification of potential geosmin-binding proteins in grass carp gill based on affinity responsive target stability and tandem mass tag proteomics - Jun-ming Zhang; Huan Han; Bing Fu; Yi-chao Li; Kang Li; Jing-wei Liu; Er-meng Yu; Li-ping Liu (Ecotoxicology and Environmental Safety)
The escalating issue of water pollution, especially the accumulation of organic off-flavor pollutants, poses significant challenges. Geosmin, a typical off-flavor compound in aquatic environments, not only compromises the quality of aquatic products but also deters consumers. Its impact extends to aquatic organisms, with current research focusing on dose-response and ecotoxicity, while neglecting the molecular-level study of geosmin-binding proteins. This study employs an integrated approach combing affinity-responsive target stability in vitro, tandem mass tag proteomics in vivo, and molecular docking to identify geosmin-binding proteins in the gill tissue of grass carp (Ctenopharyngodon idella). ARTS analysis identified 56 proteins, predominantly membrane-associated proteins, such as catenin beta-1, annexin, and integrin beta. Proteomic analysis revealed 256 differentially expressed proteins in geosmin-exposure group, with 18 common proteins screened by in vivo and in vitro methods. Among these, annexin, cathepsin D, and interleukin-1 receptors were highlighted as potential geosmin targets, with annexin demonstrating the highest binding affinity in silico. This study provides a robust protocol integrating in vivo, in vitro, and in silico approaches to elucidate geosmin's target proteins in grass carp gill tissue, advancing our understanding of pollutant-biological interactions and enhancing environmental risk assessment accuracy.